Some Properties Of Epikarst Drainage System In Gunung Kidul Regency, Yogyakarta, Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT The aim of the paper is to enlighten some properties of epikarst drainage system due to various local condition. Karst area covered in this paper is the western part of Gunung Sewn Karst extending nearly 2/3 of the karstified areas. It belongs to Gunung Kidul Regency, Yogyakarta Special Province, Java-Indonesia. The variables identified and measured in the field include secondary porosity and the general feature of geomorphological and hydrological condition. Laboratory analysis was also conducted to acquire data of rock, Willed material porosity and texiiire gfinfilled material. Drainage system of Gunung Sewu Karst varies in some localities. The properties of epikarst drainage system is seemingly governed by lithology and geological structure. Since lithology and geological structure are controls of karst type, the drainage system variation is related to the karst type as well.